Transendensi Gerak Substansial Mulla Sadra dalam Rekonstruksi Prinsip-Prinsip Pendidikan Islam - Zaenal Saleh; Azizah Saad Said (CV. ITTC INDONESIA, 2026)
The discourse of contemporary Islamic education, particularly in Indonesia, is marked by an indeterminacy of foundational principles, resulting in their partial and normative interpretation. Consequently, Islamic education tends to be pragmatic and reactive toward modernity, lacking a solid philosophical or ontological construction. This condition undermines the teleological orientation of forming insan kamil as the ultimate goal of Islamic education, thereby losing a consistent transcendental paradigmatic framework. This study contributes to the reconstruction of the foundational principles of Islamic education through an in-depth examination of the concept of substantial motion (al-ḥarakah al-jawhariyyah) in the philosophy of Mullā Ṣadrā. Substantial motion is understood as an essential transformation occurring within existence (wujūd), rather than a mere accidental change. Within the context of Islamic education, this concept offers a paradigm shift: education is not merely the transmission of knowledge, but an existential transformation of the learner toward spiritual and intellectual perfection. Through library research employing a qualitative-philosophical approach and descriptive-analytical method, this study analyzes Mullā Ṣadrā’s seminal work Al-Ḥikmah al-Mutaʿāliyah, alongside relevant supporting literature. The findings reveal that the principles of Islamic education can be reconstructed within the framework of transcendental theosophy, which integrates ontological, epistemological, and spiritual dimensions. The study concludes that Mullā Ṣadrā’s transcendental philosophy provides a significant contribution to formulating holistic educational principles—centered on existential transformation and rooted in spiritual values. These insights open new avenues for curriculum development and redefine the role of the educator as a guide in the learner’s existential journey.